ChemInform Abstract: Syntheses, Crystal Structure, Electrochemistry and Luminescence Properties of Lanthano‐Germanotungstates. Issue 10 (February 2016) - Gupta, Rakesh; Hussain, Firasat; Behera, J. N.; Bossoh, Amoassi Martin; Mbomekalle, Israel Martyr; de Oliveira, Pedro
Abstract: Na3 K10 [La(α‐GeW11 O39 )2 ] ·27H2 O(I), Na3 K10 [Ce(α‐GeW11 O39 )2 ] ·28H2 O (II) and the acetate‐bridged hybrid dimeric complexes Na6 K6 [{Pr(μ‐OAc)GeW11 O39 (H2 O)}2 ] ·25H2 O (III), Na4 K8 [{Nd(μ‐OAc)GeW11 O39 (H2 O)}2 ] ·22H2 O (IV), and Na3 K9 [{Sm(μ‐OAc)GeW11 O39 (H2 O)}2 ] ·19H2 O (V) are prepared by reacting a trilacunary Na10 [GeW9 O34 ] precursor with Ln(NO3 )3 (Ln: La, Ce, Pr, Nd, Sm) in a KOAc buffer at pH 4.7 followed by slow solvent evaporation (60 °C, 1 h; yields of 53—59% after 4—5 weeks).